MiRNA-301b-3p induces proliferation and inhibits apoptosis in AML cells by targeting FOXF2 and regulating Wnt/β-catenin axis. (June 2022) - Lu, Yang; Zhong, Liang; Luo, Xu; Liu, Chen; Dan, Wenran; Chu, Xuan; Wan, Peng; Zhang, Zhonghui; Wang, Xiao; Liu, Zhenyan; Liu, Beizhong
Abstract: Background: MiRNA-301b-3p functions as an oncomiRNA or tumor suppressor, and has been reported in various cancer types, including pancreatic, colorectal, oral, hepatocellular and lung cancers. Although the expression of miRNA-301b-3p is upregulated in acute myeloid leukemia (AML), its biological function and precise mechanisms remain unclarified. This study explores the roles of miRNA-301b-3p in AML, with the aim of ascertaining its regulatory action on Wnt/β-catenin axis by targeting Forkhead box F2 (FOXF2). Methods: The expression levels of miRNA-301b-3p and FOXF2 were measured by quantitative real-time PCR. The effects of miRNA-301b-3p knockdown and overexpression on cell proliferation were evaluated by CCK8 and cell counting assays, while cell apoptosis was analyzed by flow cytometry. The expression levels of apoptosis-related proteins, including FOXF2, and other targets in Wnt/β-catenin axis were determined by immunoblotting. Possible interaction between miRNA-301-3p and FOXF2 in AML cells was examined by luciferase reporter assays. Results: MiRNA-301b-3p was dramatically upregulated in AML cells, and showed a negative correlation with FOXF2 expression. Downregulation of miRNA-301b-3p suppressed proliferation and promoted apoptosis in AML cells. MiRNA-301b targeted FOXF2 to regulate Wnt/β-catenin axis. In the rescue experiments, FOXF2 overexpression partly reversed the effect of miRNA-301b-3p mimic in AML cells. Conclusion: The current findings demonstrate that miRNA-301b-3p targets FOXF2 to induce proliferation and inhibit apoptosis in AML cells via regulation of Wnt/β-catenin axis. Highlights: MiR-301b-3p is frequently upregulated in AML, and miR-301b-3p overexpression facilitates the cell proliferation of AML cells. MiR-301b-3p is involved in the progression of AML by directly targeting FOXF2. MiR-301b-3p promotes the activation of Wnt/β-catenin signaling in AML through a direct targeting of FOXF2.